(untitled) (Bangladesh Heart Journal, 2021)
Anomalous origin of the coronary arteries is a very rare phenomenon and is seen only in less than 1% of the general population. Single coronary artery (SCA) is a congenital anatomic abnormality identified by a single coronary ostium giving rise to one coronary artery. Our case presented at 40 years with intermittent chest discomfort, effort intolerance and a history of getting Streptokinase one month back due to AMI (Inferior). Diagnosis was confirmed with elective conventional coronary angiography and coronary CT angiography as an extremely rare variant of the left main coronary artery (LMCA) branching off from the right coronary artery (RCA) and then following a pre-pulmonic course. We did Off Pump CABG surgery with four grafts and discharged the patient uneventfully with guidelinedirected medical therapy with a beta-blocker, statin, and dual antiplatelet agents and the patient is on follow up. Bangladesh Heart Journal 2021; 36(1) : 61-66